Students' effort allocation to their perceived strengths and weaknesses: The moderating effect of instructional strategy. (April 2019) - Hiemstra, Djoerd; Van Yperen, Nico W.; Timmerman, Marieke E.
Abstract: To become competent professionals, students should work on both their strengths and weaknesses. Considering students' limited amount of time and energy to work on multiple subjects, it is important to know what determines their allocation of effort to their perceived relative strengths or weaknesses. In a series of five studies, we examined the moderating effect of instructional strategy (i.e., self-directed versus test-directed) on the within-person relation between perceived relative strength (i.e., strengths versus weaknesses) and allocated effort across multiple subjects. We used different methodologies (scenario, field, and experimental studies), research designs (within-person and mixed factorial), populations (secondary school, college, and university students), and measures of effort (intentions, self-reported, and behavioral). The results consistently indicate that students in a self-directed instructional strategy condition tend to allocate more effort to their relative strengths, whereas students in a test-directed instructional strategy condition tend to allocate more effort to their relative weaknesses. Graphical abstract: Image 1 Highlights: We examined the role of competence self-perceptions in effort allocation. We focused on competence self-perceptions at the dimensional within-person level. Students in a self-directed instructional strategy condition allocated more effort to their strengths. Students in a test-directed instructional strategy condition allocated more effort to their weaknesses. Students' effort allocation can be directed by instruction.